Feminizing Wolbachia influence microbiota composition in the terrestrial isopod Armadillidium vulgare - Jessica Dittmer (Nature Portfolio, 2018)
Abstract Wolbachia are widespread heritable endosymbionts of arthropods notorious for their profound effects on host fitness as well as for providing protection against viruses and eukaryotic parasites, indicating that they can interact with other microorganisms sharing the same host environment. Using the terrestrial isopod crustacean Armadillidium vulgare, its highly diverse microbiota (>200 bacterial genera) and its three feminizing Wolbachia strains (wVulC, wVulM, wVulP) as a model system, the present study demonstrates that Wolbachia can even influence the composition of a diverse bacterial community under both laboratory and natural conditions. While host origin is the major determinant of the taxonomic composition of the microbiota in A. vulgare, Wolbachia infection affected both the presence and, more importantly, the abundance of many bacterial taxa within each host population, possibly due to competitive interactions. Moreover, different Wolbachia strains had different impacts on microbiota composition. As such, infection with wVulC affected a higher number of taxa than infection with wVulM, possibly due to intrinsic differences in virulence and titer between these two strains. In conclusion, this study shows that heritable endosymbionts such as Wolbachia can act as biotic factors shaping the microbiota of arthropods, with as yet unknown consequences on host fitness.